MAKNA MOTIVASI DALAM LIRIK LAGU "PELUKKU UNTUK PELIKMU" KARYA FIERSA BESARI (Analisis Semiotika Ferdinand de Saussure) - Hanna Fairuz Imtinan (2023)
ABSTRACT The song "Pelukku untuk Pelikmu" by Fiersa Besari describes the reality of beauty standards that are still inherent in society, causing feelings of insecurity that are felt by the community. "Pelukku untuk Pelikmu" which is the soundtrack for the Indonesian film, namely Imperfect: Career, Love, and Scales, in which this film tells about body shaming which has an impact on the career and love story of the actor. Song lyrics are a part of music that has the ability to express human feelings and emotions. The purpose of this study is to further discuss the motivational meaning contained in the lyrics of the song "Pelukku untuk Pelikmu" by Fiersa Besari with a semiotic approach using Ferdinand de Saussure's semiotic theory and using qualitative research methods. The results of the study show that Ferdinand de Saussure's semiotic theory can explain the meaning of a song by analyzing it, where in this song there is a motivational meaning in the lyrics of the song "Pelukku untuk Pelikmu," where this song evokes the enthusiasm of listeners when they feel inferior or insecure about body shape to remain confident and it was also found that the song "Pelukku untuk Pelikmu" can motivate listeners to continue and live life that feels heavy in the form of feelings of enthusiasm and mood or a lighter feeling after hearing the song "Pelukku untuk Pelikmu" by Fiersa Besari. Keywords: Fiersa Besari, meaning, motivation, semiotics, and song lyrics.